Burden of Acute Respiratory Infections Caused by Influenza Virus, Respiratory Syncytial Virus, and SARS-CoV-2 with Consideration of Older Adults: A Narrative Review - William P. Hanage; William Schaffner (Infectious Diseases and Therapy)
Abstract Influenza virus, respiratory syncytial virus (RSV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are acute respiratory infections (ARIs) that can cause substantial morbidity and mortality among at-risk individuals, including older adults. In this narrative review, we summarize themes identified in the literature regarding the epidemiology, seasonality, immunity after infection, clinical presentation, and transmission for these ARIs, along with the impact of the COVID-19 pandemic on seasonal patterns of influenza and RSV infections, with consideration of data specific to older adults when available. As the older adult population increases globally, it is of paramount importance to fully characterize the true disease burden of ARIs in order to develop appropriate mitigation strategies to minimize their impact in vulnerable populations. Challenges associated with characterizing the burden of these diseases include the shared symptomology and clinical presentation of influenza virus, RSV, and SARS-CoV-2, which complicate accurate diagnosis and highlight the need for improved testing and surveillance practices. To this end, multiple regional, national, and global virologic and disease surveillance systems have been established to provide accurate knowledge of viral epidemiology, support appropriate preparedness and response to potential outbreaks, and help inform prevention strategies to reduce disease severity and transmission. Beyond the burden of acute illness, long-term health consequences can also result from influenza virus, RSV, and SARS-CoV-2 infection. These include cardiovascular and pulmonary complications, worsening of existing chronic conditions, increased frailty, and reduced life expectancy. ARIs among older adults can also place a substantial financial burden on society and healthcare systems. Collectively, the existing data indicate that influenza virus, RSV, and SARS-CoV-2 infections in older adults present a substantial global health challenge, underscoring the need for interventions to improve health outcomes and reduce the disease burden of respiratory illnesses. Graphical abstract and video abstract available for this article. Graphical Abstract